Clinical trial efficacy evaluation of omega-3 on seizures control of children with refractory epilepsy and attention-deficit/hyperactivity disorder - Fallah, Razieh; Eiliaei, Shiva; Ferdosian, Farzad (Iranian Journal of Child Neurology, 2018)
Objective: This study was done to answer the question that whether or not previous antiepileptic drugs with combination of omega-3 and risperidone is more efficient than previous antiepileptic drugs with risperidone alone in decreasing of seizures monthly frequency of children with refractory epilepsy and attention-deficit/hyperactivity disorder (ADHD). Methods: In a randomized clinical trial, sixty four 7-11 year old children with refractory epilepsy and ADHD who were referred to Pediatric Neurology Clinic of Shahid Sadoughi Hospital, Yazd, Iran from June 2015, were distributed into two groups, randomly. In group I, one capsule of omega-3 daily and 0.5 mg of risperidone was divided into two doses with previous antiepileptic drugs and in group II, 0.5 mg of risperidone was divided into two doses with previous antiepileptic drugs were given. The drugs use was continued for three months and the children were followed up monthly for three consecutive months. Primary outcomes included seizure monthly frequency and good response (more than 50% of reduction in seizures monthly frequency). Secondary outcome was clinical side effects. Results: 23 girls and 33 boys with mean age of 9.24+0.15(29 children in omega-3 group and 27 children in control group) were evaluated. Omega-3 therapy was effective in decreasing of seizures monthly frequency (10.41±3.92 times vs. 17.01±4.98, P = 0.03). Good response was seen in three children (11.1%) in control (95% confidence interval: 8%-22.8%) and in 9 children (20%) in Omega-3 (95% CI: 47.83%-14.17%) group, which showed that omega-3 was more effective in seizure controlling. (P=0.001) Frequency of side effects was not different in the two groups (14.8 % in control vs. 20.7% in omega-3 groups, P=0.5). Conclusion: Omega-3 might be used as an effective and safe drug in seizures control of children with refractory epilepsy and ADHD.